2016
DOI: 10.1038/srep19796
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological treatment with mirtazapine rescues cortical atrophy and respiratory deficits in MeCP2 null mice

Abstract: Loss of MeCP2 (Methyl CpG binding protein 2) in Rett syndrome (RTT) causes brain weight decrease, shrinkage of the cortex with reduced dendritic arborization, behavioral abnormalities, seizures and cardio-respiratory complications. The observed monoamine neurotransmitters reduction in RTT suggested antidepressants as a possible therapy. We treated MeCP2-null mice from postnatal-day 28 for two weeks with desipramine, already tested in RTT, or mirtazapine, an antidepressant with limited side-effects, known to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 55 publications
7
37
0
Order By: Relevance
“…Similarly, the percentage of polarized null neurons resulted significantly diminished from DIV18 (71% and 55,8% in wt and null neurons respectively, Figure 2P; see materials and methods for definition of polarized neurons). Eventually, in line with previous findings (Bittolo et al, 2016;Sampathkumar et al), NPC derived null neurons at DIV14 showed a reduction in soma size 2016; Figure 2Q).…”
Section: Npcssupporting
confidence: 91%
“…Similarly, the percentage of polarized null neurons resulted significantly diminished from DIV18 (71% and 55,8% in wt and null neurons respectively, Figure 2P; see materials and methods for definition of polarized neurons). Eventually, in line with previous findings (Bittolo et al, 2016;Sampathkumar et al), NPC derived null neurons at DIV14 showed a reduction in soma size 2016; Figure 2Q).…”
Section: Npcssupporting
confidence: 91%
“…These results are consistent with a recent mouse study in which chronic MIR dosing with 10 or 50 mg/kg failed to increased body weight relative to control animals. 42 This suggests that the adverse effects of different daily dosing regimens of MIR disappear within minutes of administration, which is consistent with its sleep-promoting effects. 19,29 This pharmacological property of MIR increases its treatment adherence and substantially improves the symptoms of depression.…”
Section: Experiments 2: Effect Of Chronic Mir Dosing On Sedationsupporting
confidence: 56%
“…Recent studies indicate that chronic dosing with MIR (50 mg/kg) restores morphological alterations, normalizes physiological functions, and reestablishes normal levels of neurotransmission in animals with characteristic symptoms of Rett syndrome. 42 Other studies have suggested that MIR can be used to treat drug withdrawal symptoms and reduce drug use in substance abusers. 22,48 These results support the clinical observation that chronic dosing with MIR does not produce sedation, a pharmacological property that can increase treatment adherence and substantially improve symptoms of depression.…”
Section: Resultsmentioning
confidence: 99%
“…Also, as Trolox ameliorated only a few of the multiple complex Rett symptoms, one may consider its use as adjuvant, i.e., its combination with other compounds improving different symptoms, in order to complement the spectrum of effects. For example, respiration, which was not improved by Trolox was shown earlier to be normalized by norepinephrine uptake blockers, GABA uptake inhibitors, and serotonin 1a receptor agonists (Zanella et al, 2008; Abdala et al, 2010) or the antidepressant mirtazapine which furthermore prevented cortical atrophy (Bittolo et al, 2016). In view of the complex phenotype of RTT, such combination therapies, designed to the particular needs of each individual patient are probably the most promising but also the most challenging strategy.…”
Section: Discussionmentioning
confidence: 98%